Responsiveness and Minimal Clinically Important Difference of the Brief-BESTest in People with COPD after Pulmonary Rehabilitation - Paixão, Cátia (2021)
Objective: The Brief-Balance Evaluation Systems Test (Brief-BESTest) is a comprehensive, reliable and valid balance test, which provides valuable information to guide balance training in people with COPD. Its clinical interpretability is, however, currently limited, as cutoff points to identify clinical relevant changes in people with COPD, after pulmonary rehabilitation (PR), are still lacking. This study aimed to establish the responsiveness and minimal clinically important difference (MCID) for the Brief-BESTest in people with COPD, after PR. Methods: A secondary analysis of data from two previous studies was conducted. The modified British Medical Research Council (mMRC) dyspnea scale, the six-minute walk test (6MWT) and the Brief-BESTest (0-24 points) were collected in people with COPD pre/post a 12-week PR program including balance training. The MCID was computed using anchor- and distribution-based methods. Changes in the 6MWT and the mMRC were assessed and used as anchors. The pooled MCID was computed using the arithmetic weighted mean (2/3 anchor- and 1/3 distribution-based methods). Results: Seventy-one people with COPD (69±8 years; 76% male; FEV1 49.8±18% predicted) were included. There was a significant improvement in the Brief-BESTest after PR (mean difference 3±3 points; p<0.001). Significant correlations were found between the Brief-BESTest and the mMRC (r=-0.31; p=0.008), and the 6MWT (r=0.37; p=0.002). The pooled MCID was 3.3 points. Conclusion: An improvement of at least 3 points in the Brief-BESTest in people with COPD will enhance the interpretability of PR effects on balance performance of this population and guide tailored interventions. Impact: This study reports on the responsiveness and the MCID of the Brief-BESTest, in people with COPD following PR. This outcome measure is comprehensive, easily administered and simple to interpret in clinical practice. This study represents a significant contribution for the clinical interpretation of changes in balance in people with COPD, following PR.